Forty years of the Landless Workers Movement : landless perspectives - Flynn, Alex (Anthropologist) (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"Landless Perspectives: 40 Years of the Landless Workers Movement presents ethnographic insights into Latin America's largest social movement as it celebrates its 40th anniversary. The Landless Workers Movement (MST), with over 1.5 million members, has been fighting for agrarian reform since 1984. In its forty-year struggle, the movement has secured land for over 350,000 families and become a worldwide beacon for progressive politics. Its enduring presence is a remarkable feat; while other movements have come and gone, the MST continues to be a steadfast force in the pursuit of social justice and environmental sustainability. How has the MST managed to endure in a country dominated by agribusiness and characterized by a hostile politics? The rationale of this collection is to answer such questions from an ethnographic standpoint, connecting personal stories to theorizations of land and struggle. The detailed accounts of the book's contributions sit in dialogue with the longitudinal commitment of the contributors, many of whom have been working with the movement over a period of decades. Such a commitment allows the book to speak to a forty-year timeframe, creating an approach that points to broader conclusions and possible futures. With contributors from Brazil, Europe and North America, the book connects lived experiences with wider political questions pertaining to global mass mobilization. Offering a fresh perspective on one of the world's most iconic social movements, the volume will be of interest to scholars of anthropology, sociology, political science, Latin American studies and beyond"--
Keywords: Movimento dos Trabalhadores Rurais sem Terra (Brazil); Social movements -- Latin America; SOCIAL SCIENCE / Anthropology / Cultural